The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12978-017-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with intimate partner physical violence among women attending antenatal care in Shire Endaselassie town, Tigray, northern Ethiopia: a cross-sectional study, July 2015

Abstract: Background: Intimate partner physical violence is a common global phenomenon. About 30.00% and 38.83% of women in the world and in sub-Saharan Africa experienced physical violence by their partner respectively in 2013. Though intimate partner violence has serious adverse health consequences, there is limited information about partner violence during pregnancy in Ethiopia. Therefore, the aim of this study was to assess the prevalnce of physical intimate partner violence during pregnancy and associated factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
82
6
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 23 publications
27
82
6
3
Order By: Relevance
“…e prevalence of intimate partner violence in this study is more than two times compared to the findings in Nigeria (14.8%) [29], Namibia (8%) [3], South Africa (15%) [30], and Brazil (15.5%) [31] and a study in Yirgalem, Ethiopia, (12%) [10]. It is also higher than the findings from Rwanda (29.2%) [12] and Ethiopia (Shirendasilase (20.6%) [9], Hulet Ejunesie (32.2%) [32], and Gonder (25.4%)) [18]. e possible explanation for the variation might be due to the difference in the accessibility of information on gender-based issues and reproductive health information and cultures of the study subjects.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…e prevalence of intimate partner violence in this study is more than two times compared to the findings in Nigeria (14.8%) [29], Namibia (8%) [3], South Africa (15%) [30], and Brazil (15.5%) [31] and a study in Yirgalem, Ethiopia, (12%) [10]. It is also higher than the findings from Rwanda (29.2%) [12] and Ethiopia (Shirendasilase (20.6%) [9], Hulet Ejunesie (32.2%) [32], and Gonder (25.4%)) [18]. e possible explanation for the variation might be due to the difference in the accessibility of information on gender-based issues and reproductive health information and cultures of the study subjects.…”
Section: Discussioncontrasting
confidence: 51%
“…e other difference could also be that findings from Ethiopia (Shirendasilase [9] and Yirgalem [10]) measured only physical violence, but in this study, three types of violence (psychological, physical, and sexual violence) were included. e association between respondents and their partner's sociodemographic and other-related characteristics and experiences of violence was assessed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On reaction to the abuse, the study found that significant percentage of the abused women kept the assault secret while others reported to some persons. This is similar to finding from other studies, [19][20][21][22][23][24][25][26][27][28][29] 28 This is surprising considering the fact that more than one third of the abused women had higher education. This calls for greater enlightenment and education to pregnant women that domestic violence is not excusable at all.…”
Section: Discussionsupporting
confidence: 75%
“…This rate is lower compared that found in the study by Boufettal H et al where it was estimated at 12.3% in Morocco [15]. In Ethiopia, nearly one fifth (20.6%) of the women interviewed were physically abused by intimate partners during pregnancy [16]. The situation is all the more worrying in a study carried out in Brazil where 49.6% were subjected to violence during their pregnancy [17].…”
Section: State Of Victims and Perpetrators At Time Of The Assaultmentioning
confidence: 61%